2018
DOI: 10.1128/jvi.01957-17
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity in Rabbits of HIV-1 SOSIP Trimers from Clades A, B, and C, Given Individually, Sequentially, or in Combination

Abstract: Recombinant soluble HIV-1 envelope glycoprotein (Env) SOSIP trimers are a design platform for inducing broadly neutralizing antibodies (bNAbs) by vaccination. To date, these and alternative designs of native-like trimers, given singly or in pairs, have not induced bNAbs in test animals such as rabbits or macaques. Here, we have evaluated whether trivalent and tetravalent combinations of SOSIP trimers from clades A, B, and C, delivered simultaneously or sequentially, induce better neutralizing antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 27 publications
(73 reference statements)
5
85
0
Order By: Relevance
“…We observed that immunization with a combination of immunogens in a cocktail formulation or in sequence did not induce bNAbs, but merely autologous NAb responses. Furthermore, the autologous NAb responses were prominent against the most immundominant trimer of the cocktail [69]. Thus, the immune response shows narrow specificity, similar to what has been reported for influenza vaccines [74].…”
Section: Evaluating Env Trimers In Vivo: Learning From Different Immusupporting
confidence: 76%
See 2 more Smart Citations
“…We observed that immunization with a combination of immunogens in a cocktail formulation or in sequence did not induce bNAbs, but merely autologous NAb responses. Furthermore, the autologous NAb responses were prominent against the most immundominant trimer of the cocktail [69]. Thus, the immune response shows narrow specificity, similar to what has been reported for influenza vaccines [74].…”
Section: Evaluating Env Trimers In Vivo: Learning From Different Immusupporting
confidence: 76%
“…One strategy to counteract the immunogenicity of the BG505 specific glycan hole would be to immunize with trimers that contain glycans at positions N241 and N289. Previous studies have shown that immunizations with trimers based on isolates with a denser glycan shield (AMC008 and ZM197M) induced a broader heterologous NAb response compared to trimers from isolates with large holes in the glycan shield (BG505 and B41), which supports the pursuit of this strategy [69].…”
Section: Evaluating Env Trimers In Vivo: Learning From Immunization Ementioning
confidence: 62%
See 1 more Smart Citation
“…449 In conclusion, we provide evidence that protein immunization with native-like Env 450 trimers can induce potent and protective nAb titers in the SHIV/macaque model. Thus, 451 nAb-mediated protection from Tier 2 virus challenge is not limited to bnAbs, which are 452 generally focused to a single site of vulnerability and have a defined effector-function 453 profile, but can also be accomplished by polyclonal autologous nAb responses of 454 sufficient magnitude and specificity, which comprise a broad range of neutralizing and 455 non-neutralizing antibody lineages to various, often overlapping epitopes that interact in 456 both synergistic or competitive ways (Klasse et al, 2018;Pauthner et al, 2017;Sanders 457 et al, 2015;Torrents de la Peña et al, 2018). The protective nAb titer threshold against 458 the homologous challenge virus that we determined is in rough accord with passive 459 antibody transfer studies and provides a benchmark for comparison with upcoming 460 antibody protection studies against HIV in humans (www.ampstudy.org).…”
Section: Discussion 417mentioning
confidence: 99%
“…NAb specificities to the N355-region were observed in BG505 SOSIP immunized rabbits 256 (Klasse et al, 2018), and were detected in week 0 plasma of animal 12-137 using electron 257 microscopy based serum mapping ( Figure S3C) (Bianchi et al, 2018). We could further 258…”
Section: Robust Protection Of High Nab Titer Group Nhps 168mentioning
confidence: 99%